Dye-based qPCR assays for the separate quantification of total bacterial, fungal, arthropod, and plant DNA - Teresa M. Tiedge; Kim R. Love; Kelly A. Meiklejohn (PLoS ONE, 2026)
Characterization of bacterial, fungal, arthropod, and plant communities from bulk environmental samples can enhance our understanding of the biodiversity on Earth and aid in biomonitoring of various biomes. An important step in any molecular biology protocol is DNA quantification. While fast methods that determine the total amount of DNA in a sample are widely available, quantitative polymerase chain reaction (qPCR) is often preferred as it permits quantification of specific DNA molecules of interest. Currently, commercial qPCR assays are only available to quantify total bacterial and fungal DNA; limited studies describe the use of qPCR to quantify total arthropod and plant DNA. Here we describe the rigorous validation of four dye-based qPCR assays to separately quantify total bacterial, fungal, arthropod, and plant DNA following the MIQE guidelines. Validation experiments included primer annealing, primer concentration, specificity ( in vitro and in silico ), sensitivity, and reproducibility. Standard curves were created using synthetic double stranded DNA (gBlocks ™ ) that were designed to quantify the DNA molecules of interest. Melt curve temperatures were identified for each taxon for specificity confirmation. These four assays were found to be specific, sensitive, and reproducible and can quantify DNA from single source specimens and mixed DNA samples, such as environmental DNA.